2005
DOI: 10.1007/s00259-005-1876-y
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG PET in the management of endometrial cancer

Abstract: Whole-body FDG-PET coupled with MRI-CT facilitated optimal management of endometrial cancer in well-selected cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(35 citation statements)
references
References 25 publications
0
31
0
4
Order By: Relevance
“…Several reports indicated that 18 F-FDG PET is useful for managing pre-and postoperative patients with endometrial carcinoma mainly by detecting lymph node metastasis (14)(15)(16)(17). The classification of tumor characteristics determined by 18 F-FDG uptake and the 18 F-FDG-to-18 F-FES ratio could play an important role in the differential diagnosis of endometrial lesions and in deciding the therapeutic strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports indicated that 18 F-FDG PET is useful for managing pre-and postoperative patients with endometrial carcinoma mainly by detecting lymph node metastasis (14)(15)(16)(17). The classification of tumor characteristics determined by 18 F-FDG uptake and the 18 F-FDG-to-18 F-FES ratio could play an important role in the differential diagnosis of endometrial lesions and in deciding the therapeutic strategy.…”
Section: Discussionmentioning
confidence: 99%
“…As indicated by some authors, in endometrial cancer the major contribution of 18 F-FDG-PET/CT could be in the early assessment of disease recurrence after therapy [60,69]. The good performance of 18 F-FDG-PET/CT has been confirmed by Kitajima et al in a recent paper including 30 patients, that showed an overall patient-based sensitivity, specificity and accuracy of 93% [70].…”
Section: Endometrial Cancermentioning
confidence: 86%
“…Few small studies assessed the validity of PET alone in the evaluation of primary endometrial cancer, showing good levels of sensitivity (range 83.3-96.7% [59][60][61]). Torizuka et al affirmed the feasibility of PET study in the assessment of myometrial involvement, reporting a better diagnostic accuracy than MRI (86.4% versus 77.3% respectively) [59].…”
Section: Endometrial Cancermentioning
confidence: 99%
“…Nevertheless, misdiagnosis may occur in physiological urinary or gastrointestinal tract uptake studies or where there is active inflammation (which may give a false positive), while small or micrometastatic lesions may also be missed (false negative). In EMC, only a few available studies using a PET scan to predict LN metastasis have been reported [85][86][87][88] with a sensitivity of 67-73% and a specificity of 94-95% when used alone [85,86] or slightly improved when used in concurrence with a CT scan, with a sensitivity and specificity of 53-69 and 90-99%, respectively [87,88] .…”
Section: Myometrial Invasionmentioning
confidence: 99%